Assessing creativity: an index proposal. Issue 1 (2nd January 2018) - Castro-Higueras, Antonio; de Aguilera-Moyano, Miguel
ABSTRACT: Creativity as a driving force for the economy of a region is the subject of a large body of research that aims to assess this concept by means of a system of indicators. Our research is based on the idea that each dimension of this theory can be grouped into three main structures: a creative base, public policies and creative industry output. In order to contrast this hypothesis, we have created a system of indicators that is based on the analysis and review of existing indicators, grouping them into the three aforementioned domains. By applying these indicators to a practical case, namely to the three largest cities in Andalusia, we have identified the connections that exist between these domains, while also establishing a creativity ranking list. We have named this indicator proposal, The Potentiality of Creative Industries Index, due to the potential value to be obtained from the analysis of the connections that exist between the aforementioned three vectors. The aim of this study is to propose an analysis tool that will facilitate the design and implementation of effective public policies in the field of creative industries.